If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 159 + -2x = 25x + 15 Reorder the terms: 159 + -2x = 15 + 25x Solving 159 + -2x = 15 + 25x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-25x' to each side of the equation. 159 + -2x + -25x = 15 + 25x + -25x Combine like terms: -2x + -25x = -27x 159 + -27x = 15 + 25x + -25x Combine like terms: 25x + -25x = 0 159 + -27x = 15 + 0 159 + -27x = 15 Add '-159' to each side of the equation. 159 + -159 + -27x = 15 + -159 Combine like terms: 159 + -159 = 0 0 + -27x = 15 + -159 -27x = 15 + -159 Combine like terms: 15 + -159 = -144 -27x = -144 Divide each side by '-27'. x = 5.333333333 Simplifying x = 5.333333333
| 2-3=11 | | 3(3x-2)+17=7x+3 | | -31x-2x=5-8x | | 13x^2+5x-8=0 | | 5xy+7=62 | | X^2+5x=x^2-x-12 | | 6x-5=4x+15 | | 9x+10(2x+33000)=45640 | | -4-11=4r+21 | | -9=t-11 | | 2x+8=64-5 | | 12-9x=157-44x | | 2-ax=-8 | | x^3+3x=85 | | .333(x-2)=4 | | 5x+10(3x+44000)=513000 | | 7xy+2yx+8xy= | | 3x-8(4x-6)+8(x+4)=0 | | X-4x=-25+3+22 | | s-14.2=-18.7 | | 5(x-3)-2(x+1)=4 | | (5x^2+7x)(12x^2-5x-3)=0 | | 3x+15=74-3x | | -9x+23=88 | | -24+18= | | p+(-26)=-13.8 | | (x^2-xy+y^2)+3xy=0 | | 2f-3g+5g-6f= | | a+6b+a+5c= | | 3[5-3(5-t)]-5=5[3(5t-5)+10]-45 | | s(x)=.5x^2-8x+34 | | 3(y+2)=16*2y |